An Experiment in Candidate Selection - Casey, Katherine; Kamara, Abou Bakarr; Meriggi, Niccoló F. (American Economic Review, 2021)
Are ordinary citizens or political party leaders better positioned to select candidates? While the American primary system lets citizens choose, most democracies rely instead on party officials to appoint or nominate candidates. The consequences of these distinct design choices are unclear: while officials are often better informed about candidate qualifications, they may value traits, like party loyalty or willingness to pay for the nomination, at odds with identifying the best performer. We partnered with both major political parties in Sierra Leone to experimentally vary how much say voters have in selecting Parliamentary candidates. Estimates suggest that more democratic procedures increase the likelihood that parties select voters’ most preferred candidates and favor candidates with stronger records of public goods provision. (JEL D72, H41, O17)